2018
DOI: 10.2147/cmar.s186563
|View full text |Cite
|
Sign up to set email alerts
|

Germline <em>BRCA1</em> and <em>BRCA2</em> deleterious mutations and variants of unknown clinical significance associated with breast/ovarian cancer: a report from North India

Abstract: BackgroundThe spectrum of BRCA mutations that predispose to development of breast/ovarian cancer in Indian population remains unexplored. We report incidence and various types of pathogenic, likely pathogenic and variants of unknown significance (VUS) mutations in BRCA1 and BRCA2 genes observed at a tertiary cancer center in North India.Materials and methodsA total of 206 unrelated breast and/or ovarian cancer patients, who met the National Comprehensive Cancer Network (NCCN) guidelines for genetic testing, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 39 publications
(40 reference statements)
2
25
1
Order By: Relevance
“…8 - 10 Inherited mutations in the key tumor suppressor genes, the breast cancer susceptibility gene 1 or 2 ( BRCA1 or BRCA2 ), are prevalent in 3%-27% of patients with ovarian cancer who are not selected on the basis of clinical features like family history. 11 , 12 By age 70 years, ovarian cancer risk is 40% in BRCA1 and 18% in BRCA2 mutation carriers. 13 Germline mutations in BRCA genes also confer high risk for the development of fallopian tube carcinoma and primary papillary serous carcinoma of the peritoneum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 - 10 Inherited mutations in the key tumor suppressor genes, the breast cancer susceptibility gene 1 or 2 ( BRCA1 or BRCA2 ), are prevalent in 3%-27% of patients with ovarian cancer who are not selected on the basis of clinical features like family history. 11 , 12 By age 70 years, ovarian cancer risk is 40% in BRCA1 and 18% in BRCA2 mutation carriers. 13 Germline mutations in BRCA genes also confer high risk for the development of fallopian tube carcinoma and primary papillary serous carcinoma of the peritoneum.…”
Section: Introductionmentioning
confidence: 99%
“…22 - 26 For example, the recent National Comprehensive Cancer Network guidelines (version 1, 2020) recommend genetic testing for BRCA1 / 2 mutations along with other panels of mutations like CDH1 , PALB2 , PTEN , and TP53 in patients with breast cancer, ovarian cancer, and pancreatic cancer on the basis of their family history, ethnicity, age, and tumor histology. 27 Although a few regional studies have been reported, 11 , 28 , 29 these have included patients with breast and/or ovarian cancer who were chosen because of clinical features like suggestive family history or young age, with pathogenic or likely pathogenic mutation being reported in 25.5%-30.1% of them. Hence, this multicenter Indian study was undertaken in patients with ovarian cancer not selected for any predisposing clinical features, who were evaluated for prevalence of germline BRCA mutations and its association with clinical and pathologic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, BRCA2 variants ch13:32906547 (c.937_938insT) and chr13:32906565 (c.956_957insA) were confirmed as FP. Mehta et al (2018) reported these variants as true germline mutations in Indian patients with breast cancer and the coverage data and Sanger validation were not reported (14).…”
Section: Discussionmentioning
confidence: 99%
“…Many factors can contribute in the etiology of ovarian tumors, and these may include genetic mutation such as Breast Cancer (BRCA) mutation (44)(45)(46)(47), postmenopausal stage (48), talcum powder (49) and hormonal change in advance age (50). Generally this type of cancer is considered to be one of the most devastating tumors, due to the lack of specific clinical symptoms related to it, until to be spread beyond level of the primary site and become difficult to treat (50).…”
Section: Discussionmentioning
confidence: 99%